Utilization dyeing process of coffea pigment as superhydrophobic coating on fabric application - Marsi, Noraini; Zakaria, Athirah; Mohd Rus, Anika Zafiah; Mahmood, Salwa (Penerbit UTHM, 2020)
Synthetic pigments and dyes was frequently used for textile products in order to fulfill the customers demand because it is less expensive and high durability compared to natural pigments or dyes. Therefore, the contribution of synthetic dyes waste water is higher and it becomes one of cause of hazardous pollution to the environment. Factories that discharge this dye waste water are harmful toxic waste and high chemical usage which can give a bad effect to the human health [1]. An alternative way need to be considered in order to overcome the problems that comes from the synthetics dyes. The alternative way that were studied in this project as the solution to the problems stated was by using natural resources which is coffee as a colorant for pigmentation or dyeing in order to replace the harmful synthetic dyeing [2]. Robusta coffee or Coffea canephora is chosen as the pigments colorant because it has minimal environmental impacts compare to synthetic pigments. Natural pigments are not harmful to the environment, which makes it so captivating for consumers. Natural pigments are biodegradable and disposing them will not lead to pollution [3]. Furthermore, natural pigments are safe to use. It does not cause any harm or health problem when abstain. Pigment appearance is altered by selective absorption and by scattering of light [4]. Other than that, different composition of natural pigments can give a wide-range of colour by modifying the concentration percentage of pigments ingredients such as Robusta coffee which brew for pigments in order to provide a varied brown colour to textile fabrics. The superhydrophobic coating fabrics for textile application provide a durable water repellent which is useful for fabrics in order to protect them from water. In addition, the fabric also can be easily clean [5].